Inactivation of Human Norovirus and Tulane Virus by High Pressure Processing in Simple Mediums and Strawberry Puree - DiCaprio, Erin; Ye, Mu; Chen, Haiqiang; Li, Jianrong (Frontiers in Sustainable Food Systems, 2019)
Human norovirus (NoV) is a major cause of fresh produce associated outbreaks. In this study a non-thermal process, high pressure processing (HPP), was evaluated for efficacy against a human NoV GII.4 strain, and Tulane virus (TV). Virus survival following HPP treatment was determined using direct quantitative reverse transcriptase PCR (RT-qPCR), the porcine gastric mucin magnetic bead (PGM-MB) binding assay followed by RT-qPCR, and plaque assay. HPP (400 MPa) inactivation of human NoV and TV was enhanced in simple mediums at a low initial temperature (4°C) and neutral pH (pH 7). HPP treatment of human NoV and TV in strawberry puree at 400 MPa did not significantly affect the level of RNA detected using the PGM-MB binding assay; increasing the pressure level to 600 MPa lead to inactivation of both human NoV and TV. Overall, HPP inactivation of human NoV GII.4 and TV is enhanced at lower initial temperature and neutral pH, and viruses can be inactivated in the food matrix at commercially acceptable pressure levels.